Malignant mesotheliomas in former miners and millers of crocidolite at Wittenoom (Western Australia) after more than 50 years follow-up - Berry, G.; Reid, Alison; Aboagye-Sarfo, P.; De Klerk, N.; Olsen, N.; Merler, E.; Franklin, P.; Musk, A. (2012)
Background: To report the number of malignant pleural and peritoneal mesotheliomas that have occurred in former Wittenoom crocidolite workers to the end of 2008, to compare this with earlier predictions, and to relate the mesothelioma rate to amount of exposure. Methods: A group of 6489 men and 419 women who had worked for the company operating the former Wittenoom crocidolite mine and mill at some time between 1943 and 1966 have been followed up throughout Australia and Italy to the end of 2008.Results:The cumulative number of mesotheliomas up to 2008 was 316 in men (268 pleural, 48 peritoneal) and 13 (all pleural) in women. There had been 302 deaths with mesothelioma in men and 13 in women, which was almost 10% of all known deaths. Mesothelioma rate, both pleural and peritoneal, increased with time since first exposure and appeared to reach a plateau after about 40 to 50 years. The mesothelioma rate increased with amount of exposure and the peritoneal mesotheliomas occurred preferentially in the highest exposure group, 37% compared with 15% overall. Conclusion: By the end of 2008, the number of mesothelioma deaths had reached 4.7% for all the male workers and 3.1% for the females. Over the past 8 years the numbers were higher than expected. It is predicted that about another 60 to 70 deaths with mesothelioma may occur in men by 2020. © 2012 Cancer Research UK All rights reserved.